Legal Liability of 'Free-Riders' during the COVID-19 Pandemic: A Mere Negligent Public Nuisance or Reckless Public Health Offence? (Dhaka University Law Journal, 2022)
Abstract not availableDhaka University Law Journal, Vol. 32(1), 2021 P.174-195